Mapping new pharmacological interventions for cognitive function in Alzheimer’s disease: a systematic review of randomized clinical trials - Xu Lou, Inmaculada; Chen, Jiayue; Ali, Kamran; Shaikh, Abdul Lateef; Chen, Qilan (Frontiers in Pharmacology, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is characterized by cognitive decline. To date, there are no effective treatments for AD. Therefore, the objective of this study was to map new perspectives on the effects of pharmacological treatment on cognitive function and the overall psychological state in patients with AD. Two independent researchers searched for randomized clinical trials (RCTs) exploring new pharmacological approaches related to cognition in Alzheimer's disease in adults from 2018 to 2023 in PubMed, Web of Science, Scopus, and Cochrane Library databases. A total of 18 RCTs were included in this review. The results show that in recent years, new drugs have been tested in patients with Alzheimer's disease, including masitinib, benfotiamine, methylphenidate, levetiracetam, Jiannao Yizhi, and Huannao Yicong formulas. Most studies have been conducted in populations with mild to moderate Alzheimer's disease. Although some of the drugs found suggested improvement in cognitive function, the scarcity of available studies highlights the need for further research in this area.